2021
DOI: 10.51963/jers.v23i3.2016
|View full text |Cite
|
Sign up to set email alerts
|

Insecticide Resistance in the Brown Planthopper, Nilaparvata lugens (Stål): Mechanisms and Status in Asian Countries

Abstract: The brown planthopper, Nilaparvata lugens (Stål) is a destructive rice pest found in almost all the rice-growing areas across the globe. In pest management strategies, insecticides are the vital element to control this insect pest. But recently their heavy use poses a risk of control failure because of the development of insecticide resistance. Quick insecticide resistance development nature in N. lugens intrigued scientists to understand the complex resistance mechanism(s), side by side pledge the importance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 54 publications
(89 reference statements)
0
5
0
Order By: Relevance
“…Many studies identified metabolic resistance mechanism, increased detoxification enzyme, as the main mechanism that contributes to resistance development in BPH. Increased enzyme activities of P450, GST, and EST were found responsible for resistance development in BPH (Datta & Banik 2021). We found increased activities of P450 in imidacloprid resistant-BPH.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Many studies identified metabolic resistance mechanism, increased detoxification enzyme, as the main mechanism that contributes to resistance development in BPH. Increased enzyme activities of P450, GST, and EST were found responsible for resistance development in BPH (Datta & Banik 2021). We found increased activities of P450 in imidacloprid resistant-BPH.…”
Section: Discussionmentioning
confidence: 48%
“…Chemical control is the primary pest management strategy to manage this pest. The key chemical insecticides used to control BPH are neonicotinoids, pyrethroids, carbamates, organophosphates, and insect growth regulators (Fujii et al, 2020;Datta & Banik, 2021). However, the toxicity against BPH has been reduced and the pest also evolved low to high levels of resistance to commonly used insecticides (Datta et al, 2021b).…”
Section: Introductionmentioning
confidence: 99%
“…1,2 For a long time, chlorpyrifos, imidacloprid, thiamethoxam, pymetrozine, and buprofezin were the main insecticides used to control S. f urcifera in Sichuan; however, their long-term misuse has led to varying degrees of resistance in the field populations. 3,4 Since 2016, the field populations of S. f urcifera in the primary rice-growing regions of Sichuan have been monitored, and we found that they showed low to moderate resistance toward chlorpyrifos and thiamethoxam but were still susceptible to imidacloprid, buprofezin, and pymetrozine. 5 The resistance of S. f urcifera collected from Anhui, Hebei, Jiangxi, and Hunan were monitored, revealing that their resistance ratios (RRs) toward pymetrozine were more than 469-fold, up to 3605-fold.…”
Section: ■ Introductionmentioning
confidence: 91%
“…Sogatella furcifera (Horváth) belongs to the order Hemiptera (formerly known as Homoptera) and the family Delphacidae; It is a significant pest that primarily damages crops such as rice, corn, and sorghum by transmitting the rice black-streaked dwarf virus. As a migratory insect pest, Sogatella furcifera is among the three major planthoppers that pose a threat to rice production. , For a long time, chlorpyrifos, imidacloprid, thiamethoxam, pymetrozine, and buprofezin were the main insecticides used to control S. furcifera in Sichuan; however, their long-term misuse has led to varying degrees of resistance in the field populations. , Since 2016, the field populations of S. furcifera in the primary rice-growing regions of Sichuan have been monitored, and we found that they showed low to moderate resistance toward chlorpyrifos and thiamethoxam but were still susceptible to imidacloprid, buprofezin, and pymetrozine . The resistance of S. furcifera collected from Anhui, Hebei, Jiangxi, and Hunan were monitored, revealing that their resistance ratios (RRs) toward pymetrozine were more than 469-fold, up to 3605-fold .…”
Section: Introductionmentioning
confidence: 99%
“…Intensive and excessive application of insecticides has encouraged the emergence of BPH resistance (Datta and Banik 2021;Iamba and Dono 2021;Utari et al 2023). Various environmentally friendly controls have been recommended to reduce the BPH population, such as ecological engineering (Horgan et al 2016) and the use of natural enemies such as predators (Syahrawati et al 2015;Nasral et al 2020;Syahrawati et al 2021a;Syahrawati et al 2021b;Siregar et al 2023;Utari et al 2023), parasitoids (Minarni et al 2018;Abdilah and Susilo 2020), and insect pathogens, such as Beauveria bassiana (Hendra et al 2022;Kurniawati et al 2021;Mascarin and Jaronski 2016;Trizelia et al 2023).…”
Section: Introductionmentioning
confidence: 99%